Freshwater fish distribution - Berra, Tim M. 1943 (San Diego, Calif. : London : Academic Press, 2001)
"Fish occupy virtually every lake, stream, pond, river, creek, and tributary known. Because of their global distribution and their sensitivity to pollution and other sorts of disturbance, fish are excellent indicators of aquatic environmental health. Freshwater Fish Distribution includes details of the classification, identification, and distribution of nearly 170 families of fish.
Each account includes an accurate and high-quality illustration of selected members of that group as well as a distribution map and accompanying commentary on classification, distribution, and diversity."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Freshwater fishes; Freshwater fishes -- Classification; Fishes -- Geographical distribution